A Microwave-Assisted Three-Component Synthesis of Arylaminomethyl Acetylenes: A Facile Access to Terminal Alkynes - Jiang, Yubo; Huang, Shaojun (Synlett, 2014)
A simple, rapid, one-pot synthesis of arylaminomethyl acetylenes is achieved under microwave-assisted conditions (power = 5 W) using aromatic boronic acids, aqueous ammonia, propargyl halides, copper(I) oxide and water as the solvent. The reactions are complete within ten minutes affording good to excellent yields of the products.
Keywords: microwave-assisted; three-component; ammonia; propargyl halide; terminal alkynes